Glutathione S-Transferase Enzymes in Plant-Pathogen Interactions - Gullner, Gábor; Komives, Tamas; Király, Lóránt; Schröder, Peter (Frontiers in Plant Science, 2018)
Plant glutathione S-transferases (GSTs) are ubiquitous and multifunctional enzymes encoded by large gene families. A characteristic feature of GST genes is their high inducibility by a wide range of stress conditions including biotic stress. Early studies on the role of GSTs in plant biotic stress showed that certain GST genes are specifically up-regulated by microbial infections. Later numerous transcriptome-wide investigations proved that distinct groups of GSTs are markedly induced in the early phase of bacterial, fungal and viral infections. Proteomic investigations also confirmed the accumulation of multiple GST proteins in infected plants. Furthermore, functional studies revealed that overexpression or silencing of specific GSTs can markedly modify disease symptoms and also pathogen multiplication rates. However, very limited information is available about the exact metabolic functions of disease-induced GST isoenzymes and about their endogenous substrates. The already recognized roles of GSTs are the detoxification of toxic substances by their conjugation with glutathione, the attenuation of oxidative stress and the participation in hormone transport. Some GSTs display glutathione peroxidase activity and these GSTs can detoxify toxic lipid hydroperoxides that accumulate during infections. GSTs can also possess ligandin functions and participate in the intracellular transport of auxins. Notably, the expression of multiple GSTs is massively activated by salicylic acid and some GST enzymes were demonstrated to be receptor proteins of salicylic acid. Furthermore, induction of GST genes or elevated GST activities have often been observed in plants treated with beneficial microbes (bacteria and fungi) that induce a systemic resistance response (ISR) to subsequent pathogen infections. Further research is needed to reveal the exact metabolic functions of GST isoenzymes in infected plants and to understand their contribution to disease resistance.